Measurements of Value of Time and Transportation Benefits by using Observable Demand - Hisa MORISUGI (European Regional Science Association (ERSA), 2014)
The subjective value of time is the marginal rate of substitution between travel time and travel cost under constant utility or profit level. It is commonly referred to as the monetary appraisal of value of time or the willingness to pay for savings in travel time. This study proposes methods to measure the true value of time from observable demand functions applicable to non-business transport services modelled both for persons and freight. The methods proposed are different from all previous studies in the valuation of value of time which assumed either a specified utility function then applying true VOT under constant utility or a specified demand function applied using VOT under constant demand. This study showed the capability of the proposed methods to measure the components of the value of time, i.e., value of time as a resource and value of time as a commodity calculated independently or combined using observable demand for non-business person trips. The key factor in deriving the VOT in terms of observable demand is the application of the time-extended Royfs identity. The VOT as a resource defined by the marginal substitution ratio of transport cost and travel time is expressed as the observable transport demand and its derivatives. In deriving the VOT as a commodity, tx is a measure of disutility of traveling. VOT as a commodity varies depending on the mode, length of trip, destination, timing, among other, contrary to the VOT as a resource, which is fix regardless of those mentioned transport characteristics. The total VOT is the combination of the VOT as a resource and VOT as a commodity. Two methods are shown on how to measure the time savings benefits per VOT component in terms of observable Marshallian demand and VOT. The first method is by expressing the Marshallian demand with adjustment of the marginal utility ratio of income, . The second method is by expressing the compensated demand in terms of observable Marshallian demand. As it is the Hicksian compensated demand and VOT that need to be measured, this study succeeded in deriving the time extended Slutsky equations that relates the compensated demand and VOT to the observable Marshallian demand and VOT. The result of non-business freight trips is exactly identical to the case of VOT as a commodity for non-business person trips. The discussion of VOT for business person and freight trips will not included due to the space limit.
Keywords: 330; value of time as a resource; value of time as a commodity; value of time for freight trips; time saving benefit; R